2020
DOI: 10.1111/cei.13530
|View full text |Cite
|
Sign up to set email alerts
|

Relapse rate and renal prognosis in ANCA-associated vasculitis according to long-term ANCA patterns

Abstract: Summary Long-term observation of patients with ANCA-associated vasculitis (AAV) allows the identification of different longitudinal patterns of ANCA levels during follow-up. This study aimed to characterize these patterns and to determine their prognostic significance. All ANCA determinations performed in two university hospitals during a 2-year period were retrospectively reviewed. Patients were included in the analysis if they had high titers of anti-myeloperoxidase (anti-MPO) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…A flare in vasculitis is often accompanied by an increase in the serum ANCA level. 7 However, the patient’s serum MPO-ANCA level was lower at admission than at the evaluation prior to this admission. We hypothesise that this decrease in the MPO-ANCA level was affected by pre-treatment with PSL in the former hospital.…”
Section: Discussionmentioning
confidence: 82%
“…A flare in vasculitis is often accompanied by an increase in the serum ANCA level. 7 However, the patient’s serum MPO-ANCA level was lower at admission than at the evaluation prior to this admission. We hypothesise that this decrease in the MPO-ANCA level was affected by pre-treatment with PSL in the former hospital.…”
Section: Discussionmentioning
confidence: 82%
“…The various clinical manifestations of AAV often include a wide range of symptoms and signs due to the disorders of general status and damage to the renal, respiratory, nervous, and other systems (Hunter et al, 2020). Moreover, some of the injury complications may be fatal to life, such as acute renal failure and alveolar hemorrhage (Quartuccio et al, 2020;Oristrell et al, 2021).…”
Section: Overview Of Aavmentioning
confidence: 99%
“…Until now, some risk factors, such as PR3-ANCA positivity, age>65, lower serum creatinine and cardiovascular system involvement, have been reported, but not confirmed by other studies. ANCA has been proposed as a predictor of relapse since its entry into clinical studies (7), but the prediction of relapse based on ANCA patterns remains controversial (8)(9)(10)(11)(12)(13). Thai et al confirmed clinical outcomes and ANCA levels coincided for only 60% of the granulomatosis with polyangiitis (GPA) patients (11).…”
Section: Introductionmentioning
confidence: 99%